Spatial distribution, biometrics and volumetric estimation of Dicksonia sellowiana (Presl.) Hook (Dicksoniaceae) in an araucaria forest fragment - Jocasta Lerner; Isabel Homczinski; Rafael Henrique Roque; Keyla Karine Michalichen; Willian dos Santos Cavassim; Andrea Nogueira Dias; Afonso Figueiredo Filho (Acta Biológica Catarinense, 2021)
Dicksonia sellowiana is the only Brazilian tree fern in the Dicksoniaceae family. Due to the exploitation of its caudex for the manufacture of pots for plants, the species is endangered. The objective of this research was to analyze the spatial distribution of D. sellowiana in the araucaria forest. To obtain data, 37 sample units with 10 × 50 m each were evaluated and systematically distributed in 25-hectar permanent plots installed in the Irati National Forest. All tree ferns above 1.30 m in total height were identified and measured. To analyze the spatial distribution, three aggregation indices were used, while the total volume and the commercial volume were estimated using volumetric models. The density and population structure in height classes were calculated. The species has an average density of 83 individuals per hectare. Through the evaluation of the indices, it was verified that the species has an aggregated pattern. The estimates were 19.87 m3 .ha-1 for total volume and 11.82 m3 ha-1 for commercial volume, with more than 60% of these volumes concentrated in heights of 3.30 m to 6.30 m, which is about 40% of the population.